Crosslinking of Rabbit Fibrin in Vivo - Finlayson, J. S; Aronson, D. L (Thrombosis and Haemostasis, 1974)
Crosslinking found in clots produced in vivo by inducing thrombosis in the rabbit jugular vein was compared with that in platelet-poor rabbit plasma clots formed in vitro. Polyacrylamide gel electrophoresis of the dissolved washed clots showed that the sequence of events in vivo was the same as has previously been observed in vitro and that γ dimerization was followed by α polymerization, with extensive crosslinking being evident in even the earliest clots.